Effect of Zinc on Germination, Seedling Growth and Biochemical Content of Cluster Bean (Cyamopsis tetragonoloba (L.) Taub) - G. Thiyagarajan, J. Sekar, R. Manivasagaperumal*, S. Balamurugan, (Current Botany, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Cluster bean seeds were grown in the presence ofÃ‚Â 0, 10, 25, 50, 100,150 and 200 mgl-l of zinc sulphate solution in order to asses the effect of metal on germination, growth and biochemical changes. The results indicated that low level of zinc concentration (10 and 25 mgl-l) showed a significant increase in the germination, seedling growth and biochemical content; whereas the higher concentrations (50-200 mgl-l) decreased the same except for proline content.